Hubungan Kebiasaan Menyikat Gigi terhadap Tingkat Kebersihan Gigi dan Mulut Siswa Sekolah Dasar - Widyastuti, Nugraheni; Jumriani; Supriatna, Agus; Liasari, Ira; Apriliani, Isnul (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Dental and oral health problems are common in elementary school children, one of which is cavities. This tooth damage occurs because children often consume sweet, soft, and sticky foods whose remains remain in the mouth for a long time and are not cleaned immediately. Most tooth decay in children is not only caused by the habit of consuming sweet foods, but can also be influenced by various factors, including proper and consistent brushing habits. Tooth brushing habits also affect the level of dental and oral hygiene. This study aims to determine the relationship between tooth brushing habits and the level of dental and oral hygiene of students at SD 196 Mangasa, Bulupoddo District, Sinjai Regency. This type of research is an observational analytical study with a cross-sectional design. The data will be analyzed using univariate analysis to see the distribution of research variables and bivariate analysis with the non-parametric Mann-Whitney test to analyze the relationship between tooth brushing habits and the level of dental and oral hygiene. The results of the study showed that the description of good student tooth brushing habits was (31%) and less good was (69%) and the description of good student tooth and oral hygiene was (5%), moderate (90%), and bad was (5%). The results of the mann whitney statistical test p = 0.034 showed a significant relationship between tooth brushing habits and the level of dental and oral hygiene.  Keywords: Habits; brushing teeth; dental and oral hygiene